KEKERASAN DAN KEKUASAAN DALAM RUMAH TANGGA PADA CERPEN LA CONFIDENCE KARYA GUY DE MAUPASSANT: REPRESENTASI PATRIARKI PADA MASYARAKAT BANGSAWAN PRANCIS - Rasani, Laila Priyanka; Wardani, Abellia Anggi, Dr. (UI Scholars Hub, 2025)
This article discusses the domestic violence portrayed in Guy de Maupassant's short story La Confidence. The story centers on Marquise de Rennedou, who recounts to her friend, Baroness de Grangerie, her revenge for her husband's harsh treatment. The purpose of this study is to explain the depiction of patriarchal normalization that causes domestic violence, as viewed through the concept of power represented in La Confidence, along with the characters' efforts to resist such violence. This research employs a qualitative methodology using A.J. Greimas’s structural analysis theory, based on the actantial and functional schemes. The actantial scheme helps identify the functions and roles of characters and their relationships, while the functional scheme divides the plot to understand how the sequence of events influences the core of the short story related to the topic. Additionally, Michel Foucault's power relations theory is applied to examine how patriarchal societal norms influence men's behavior in the household, potentially leading to violence. The analysis ultimately reveals that the normalization of patriarchy in society, which elevates men's status, can be a cause of domestic violence, as illustrated in La Confidence.